Icons and abduction - Merell, Floyd; Queiroz, João (Signs - International Journal of Semiotics, 2010)
In our effort to relate abductive process to iconic semiosis, we argue that meaning begins the process of its development as an icon, and logic of abduction is the logic responsible for this iconic process. Our aim here is to explore the relationship between Peirce’s notion of abductive inference and iconic semiosis. In order properly to develop our argument, it behooves us to offer a brief introduction that includes: (i) the basic characteristics of abduction, (ii) Peirce’s concept of semiosis, (iii) Peirce’s categories of mind, and signs processes, and (iv) the nature of the iconic sign.